Feasibility and prognostic value of vasodilator stress perfusion CMR in patients with atrial fibrillation. (8th February 2021) - Pezel, T; Garot, P; Kinnel, M; Landon, V; Hovasse, T; Sanguineti, F; Champagne, S; Unterseeh, T; Louvard, Y; Morice, MC; Garot, J
Abstract: Funding Acknowledgements: Type of funding sources: None. BACKGROUND   Several studies have demonstrated the consistently high diagnostic and prognostic value of stress perfusion imaging with cardiovascular magnetic resonance (CMR). The feasibility and the prognostic value of vasodilator stress perfusion CMR in patients with atrial fibrillation (AF) is unknown, because most studies have excluded arrhythmic patients from analysis.  PURPOSE   The aim of our study was to assess the technical feasibility and the prognostic value of vasodilator stress perfusion CMR in patients with AF.  METHODS   Between 2008 and 2018, we prospectively included consecutive patients with AF referred for vasodilator stress perfusion CMR with dipyridamole. They were followed for the occurrence of major adverse cardiovascular events (MACE) defined as cardiac death or non-fatal myocardial infarction (MI). The secondary outcome was all-cause mortality. The diagnosis of AF was confirmed on 12-lead ECG before and after CMR, and patients with sinus rhythm during CMR were excluded. In the CMR protocol, to limit AF-related artifacts on cine images, an arrhythmia rejection algorithm, or real-time sequences were used. Univariable and multivariable Cox regressions for MACE were performed to determine the prognostic value of inducible ischemia or late gadolinium enhancement (LGE) by CMR.  RESULTS   Of 639 patients with AF and suspected or stable chronic CAD (72 ± 9 years, 77% men), 602 (94%) completed the CMR protocol, and among those 538 (89%) completed the follow-up (median follow-up 5.1 (3.3–7.1) years). Reasons for failure to complete CMR included AF-related ECG-gating problems (n = 17), intolerance to stress agent (n = 7), renal failure (n = 6), declining participation (n = 4) and claustrophobia (n = 3).  Stress CMR was well tolerated without occurrence of death or severe disabling adverse event. Patients without inducible ischemia or LGE experienced a substantially lower annual event rate of MACE (1.2%) than those with ischemia and without LGE (8.9%), or those with both ischemia and LGE (9.8%; p < 0.001 for all). Using Kaplan-Meier analysis, the presence of myocardial ischemia identified the occurrence of MACE (hazard ratio HR 7.56 ; 95% confidence interval CI: 4.86 – 11.80; p < 0.001) (Figure).  In a multivariable stepwise Cox regression including clinical characteristics and CMR indexes, the presence of inducible ischemia was an independent predictor of a higher incidence of MACE (HR 5.88 ; 95% CI: 3.70 - 10.07; p < 0.001) and all-cause mortality (HR 2.51 ; 95% CI: 1.47 - 4.17; p < 0.001).  CONCLUSION   Stress CMR is technically feasible and has a good discriminative prognostic value to predict the occurrence of MACE and all-cause mortality in patients with AF.